Pengembangan Modul Matematika Berbasis Learning Cycle 5E untuk Memfasiliasi Hasil Belajar di Sekolah Menengah Kejuruan - Ani, Wayan Dewi; Saryantono, Buang; Rahmawati, Fitriana (STKIP PGRI Bandar Lampung, 2023)
The research aims to find out (1) To find out the quality of the 5E Learning Cycle-based mathematics module in terms of the validity of teaching materials. (2) To find out the quality of Learning Cycle 5E-based math modules in terms of the practicality of teaching materials. (3) To determine the effectiveness of the Learning Cycle 5E-based mathematics module in terms of students' mathematical problem solving abilities. This research is a development research using the ADDIE development model. Product validation is carried out by 6 expert lecturers in accordance with their fields. Practicality questionnaire to measure the response of class XI students at SMK Negeri 7 Bandar Lampung in product trials and learning achievement tests to measure the effectiveness of the module as teaching material. Material experts on the aspect of content quality obtain an average score of 3.66 on the aspect of determination of coverage get an average score of 3.75 on the Learning Cycle 5E aspect opinion average value of 3.8 with valid criteria. Media experts in the aspect of paper size in the module obtain an average value of 3.75, in the aspect of module skin design (cover) get an average value of 3.83, in the aspect of module content design get an average value of 3.87 with valid criteria .Linguists in the aspect of sentence structure determination, understanding of messages and straightforwardness get an average score of 4 with valid criteria. The mathematics module based on Learning Cycle 5E in Mathematical Logic material is effective in terms of student learning outcomes in Mathematical Logic material which shows 17 students or 56.67% individually completed out of 30 students with an average of 74.38. Thus the Learning Cycle 5E-based learning module is effective as a teaching material for learning mathematics.